Shi'i doctrine, Mu'tazili theology : al-Sharīf al-Murtaḍā and Imami discourse - Abdulsater, Hussein Ali (Edinburgh scholarship online., 2017)
Examines the critical turn that shaped Imami Shi'ism in the 10th and 11th centuriesÃĐ́²Ớ²ƠGod is not free to act; He is bound by human ethics. To be just, He must create an individual of perfect intellect and infallible morality. People are obligated to submit to this person; otherwise eternal damnation awaits them. While these claims may be interpreted as an affront to God's power, an insult to human judgment and a justification for despotism, ShiÃ⁽Â¿i Muslims in the eleventh century eagerly adopted them in their attempts to forge a ÃǾ²Ơ℗rational' religious discourse. They utilized everything from literary studies and political theory to natural philosophy and metaphysical speculation in support of this project. This book presents the contribution of al-SharÄ±f al-MurtaÃŁÂıÃ⁴ (d. 1044) of Baghdad, the thinker most responsible for this irreversible change, which remains central to Imami identity. It analyzes his intellectual project and establishes the dynamic context which prompted him to pour the old wine of ShiÃ⁽Â¿i doctrine into the new wineskin of systematic MuÃ⁽Â¿tazili theology. ÃĐ́²Ớ²ƠKey Features Comprehensive coverage of al-MurtaÃŁÂıÃ⁴'s enormous oeuvre (running to several thousand pages) and diversity (spanning virtually all contemporary fields of knowledge) A meticulous engagement with long and dense theoretical texts that are either in manuscript form or poorly edited An orderly presentation that equips readers with an overall understanding of ShiÃ⁽Â¿i theology in its main phases while preserving the profundity of analysis The study of a little-known author whose views, nonetheless, are still a major influence for ShiÃ⁽Â¿i Muslims Examines the critical turn that shaped Imami Shi'ism in the 10th and 11th centuriesÃĐ́²Ớ²ƠGod is not free to act; He is bound by human ethics. To be just, He must create an individual of perfect intellect and infallible morality. People are obligated to submit to this person; otherwise eternal damnation awaits them. While these claims may be interpreted as an affront to God's power, an insult to human judgment and a justification for despotism, ShiÃ⁽Â¿i Muslims in the eleventh century eagerly adopted them in their attempts to forge a ÃǾ²Ơ℗rational' religious discourse. They utilized everything from literary studies and political theory to natural philosophy and metaphysical speculation in support of this project. This book presents the contribution of al-SharÄ±f al-MurtaÃŁÂıÃ⁴ (d. 1044) of Baghdad, the thinker most responsible for this irreversible change, which remains central to Imami identity. It analyzes his intellectual project and establishes the dynamic context which prompted him to pour the old wine of ShiÃ⁽Â¿i doctrine into the new wineskin of systematic MuÃ⁽Â¿tazili theology. ÃĐ́²Ớ²ƠKey Features Comprehensive coverage of al-MurtaÃŁÂıÃ⁴'s enormous oeuvre (running to several thousand pages) and diversity (spanning virtually all contemporary fields of knowledge) A meticulous engagement with long and dense theoretical texts that are either in manuscript form or poorly edited An orderly presentation that equips readers with an overall understanding of ShiÃ⁽Â¿i theology in its main phases while preserving the profundity of analysis The study of a little-known author whose views, nonetheless, are still a major influence for ShiÃ⁽Â¿i Muslims